Camels - Wexo, John Bonnett. (Wildlife Education, 1989)
Provides information on the physical characteristics, behavior, and different kinds of camels.
Cover title.
Provides information on the physical characteristics, behavior, and different kinds of camels.
Keywords: Camels / Juvenile literature.